Amyand’s hernia: which oncologic risk can be hidden in the sac? - Montali, Filippo; Baldinu, Manuel; Annicchiarico, Alfredo; Virgilio, Edoardo; Costi, Renato (Acta Biomedica Atenei Parmensis, 2022)
Amyand's hernia (AH) is a rare condition in which the appendix is found in the sac of an inguinal hernia. It occurs in only 1% of adult inguinal hernias. The herniated appendix can occasionally range varying degrees of acute inflammation up to neoplastic transformation. An appendiceal tumor can be rarely described inside the AH sac. We describe a case of gangrenous appendicitis in AH and offer a review of the literature on AH when presenting with appendicitis associated with appendiceal cancer. As of 2022, only nine cases of AH presenting with appendicitis associated with appendiceal cancer have been reported by the pertinent literature. In order of decreasing frequency, AH, AH-related appendicitis and AH-related appendicitis associated with appendiceal cancer are three rare conditions. Particular attention should be kept in each situation as diagnosis is achieved postoperatively most of the times.